Flow-diverting stents allow efficient treatment of unruptured, intradural dissecting aneurysms of the vertebral artery: An explanatory approach using in vivo flow analysis - Gölitz, Philipp (Interv Neuroradiol, 2016)
OBJECT: Our study aimed to evaluate the efficiency of flow-diverting stents (FDS) in treating unruptured, intradural dissecting aneurysms of the vertebral artery (VADAs). Additionally, the effect of FDS on the aneurysmal flow pattern was investigated by performing in vivo flow analysis using parametric color coding (PCC). METHODS: We evaluated 11 patients with unruptured, intradural VADAs, treated with FDS. Pre- and postinterventional DSA-series were postprocessed by PCC, and time-density curves were calculated. The parameters aneurysmal inflow-velocity, outflow-velocity and relative time-to-peak (rTTP) were calculated. Pre- and postinterventional values were compared and correlated with the occlusion rate after six months. RESULTS: Follow-up DSA detected 10 aneurysms occluded, meaning an occlusion rate of 91%. No procedure-related morbidity and mortality was found. Flow analyses revealed a significant reduction of aneurysmal inflow- velocity and prolongation of rTTP after FDS deployment. Concerning aneurysm occlusion, the postinterventional outflow-velocity turned out to be a marginally statistically significant predictor. A definite threshold value (–0.7 density change/s) could be determined for the outflow-velocity that allows prediction of complete aneurysm occlusion with high sensitivity and specificity (100%). CONCLUSIONS: Using FDS can be considered an efficient and safe therapy option in treating unruptured, intradural VADA. From in vivo flow analyses the postinterventional aneurysmal outflow-velocity turned out to be a potential predictor for later complete aneurysm occlusion. Here, it might be possible to determine a threshold value that allows prediction of aneurysm occlusion with high specificity and sensitivity. As fast, applicable and easy-to-handle tool, PCC could be used for procedural monitoring and might contribute to further treatment optimization.